Challenges for Diakonia in the contemporary Norwegian society - Jordheim, Kari (2015)
Diaconal actions are always conditioned and challenged by concrete contexts, and all contexts are multifaceted and require an interdisciplinary approach. This article describes challenges for diakonia in the contemporary Norwegian society through the framework of Plan for Diakonia, a plan document made for the whole Church of Norway accepted by the General Synod in 2007. The Church of Norway today is talking about diakonia as a feature of the total mission of the church, also explained as a dimension of being church. In the article the deacons’ profession and work in the parishes will be presented, but also the diaconal work which is undertaken by diaconal organizations and institutions together with and integrated into the welfare state. It goes beyond the scope of this article to look fully into the welfare state concept, but the Coordination Reform of Health Service from 2008/9 will be used as an example of how a white paper from the Ministry of Health and Care services underlines that church organizations are a great resource and important actors in the Norwegian society. In the end of the article I underline the importance for diakonia to have a clear engagement in society. The diaconal work needs to change as society changes. One cannot linger on old methods and ways; diaconal actions must develop and innovate with the world in order to understand the world.